Assistência odontológica a pessoas portadoras de HIV/AIDS na rede pública de saúde de Fortaleza : política de atenção e atuação do PSF - Camurça, Valeska Vieira (2008)
Two decades following the first cases of the Acquired Immunodeficiency Syndrome (Aids) registered in Brazil, health care for individuals living with HIV/Aids is still a significant challenge. Within this context, the need to implement an integrated health policy for this group has been frequently discussed. This is particularly relevant for oral health services, where the Family Health Program (PSF-Programa Saúde da Família) offers a potential tool to address this issue. This study has the objective of examining the political and organizational oral health strategies for people with HIV/Aids in the municipality of Fortaleza, Ceará state, and verifying the extent of oral care services in the municipal basic health structure. The methodology consisted of a qualitative and documentary study based on a systematic review of the literature and technical guidelines issued by the Ministry of Health and the secretariats of the State of Ceará and Municipality of Fortaleza. Additionally, the researchers used a quantitative approach using secondary data from the National Notifiable Diseases Health Information System (SINAN - Sistema de Informação de Agravos de Notificação). Finally, a snapshot of current conditions was taken by means of a questionnaire applied to 186 dental surgeons (DS) working in the PSF in Fortaleza. Analysis was undertaken using descriptive statistics, in particular tables and thematic maps to display the spatial distribution of the disease in Fortaleza, in addition to the literature review. Relatively little official documentation was found (policies and technical guidelines) relative to the oral health services for people living with HIV/Aids, especially at the federal level which only has articles and manuals available, mostly dealing with biosecurity and opportunistic oral lesions. The majority of official documentation was found at the municipal level. The study showed that until 2007, there were 3,311 people living with HIV/Aids in Fortaleza and that these individuals reside throughout the municipality. It was also determined that over half (58.06%) of the DS working in the PSF are aware of the presence of people with HIV/Aids in their working area, yet only 29.57% affirmed that they had treated members of this group in their health unit. The oral health care offered to this group was not equally distributed in the municipality; rather it was concentrated in a few locations, particularly the Executive Secretariat of Region II. It has been concluded that, despite international recognition given to the Brazilian National STD/Aids Program, it is necessary to move forward the debate on oral health services offered to this population group and that the treatment given to people with HIV/Aids has not been consolidated as a key component of oral health services offered by the PSF. This goes against a municipal policy already in existence directed towards this goal, thereby indicating the need for the reorganization and reorientation of the oral health care available to people with HIV/Aids.